The Effect of Service Quality, Price, and Destination Image on Customer Loyalty in the Tourism Industry in West Java - Khuan, Hendri; Putra, Wira Pramana; Muafiqie, Humaidah; Harsono, Iwan; Lau, Elfreda Aplonia (West Science Interdisciplinary Studies, 2024)
This research investigates the interrelated factors influencing customer loyalty in the tourism industry of West Java. Through a comprehensive study involving 200 respondents, we examine the impact of service quality, pricing strategies, and destination image on customer loyalty. Utilizing a quantitative analysis approach, the study employs structural equation modeling (SEM) with Partial Least Squares (PLS) to unravel the intricate relationships among these crucial constructs. The research contributes to the existing body of knowledge by offering insights into the specific dynamics shaping tourist allegiance in this unique region. Findings from the study provide practical implications for businesses, policymakers, and destination marketers, enabling them to tailor strategies that enhance customer loyalty and contribute to the sustainable growth of West Java's tourism sector.